1999
DOI: 10.1016/s0014-5793(99)00144-1
|View full text |Cite
|
Sign up to set email alerts
|

Pax6 and Pdx1 form a functional complex on the rat somatostatin gene upstream enhancer

Abstract: The somatostatin upstream enhancer (SMS-UE) is a highly complex enhancer element. The distal A-element contains overlapping Pdx1 and Pbx binding sites. However, a point mutation in the A-element that abolishes both Pdx1 and Pbx binding does not impair promoter activity. In contrast, a point mutation that selectively eliminates Pdx1 binding to a proximal B-element reduces the promoter activity. The B-element completely overlaps with a Pax6 binding site, the C-element. A point mutation in the C-element demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 47 publications
(58 reference statements)
3
32
0
Order By: Relevance
“…2C), where expression of Pdx1, Nkx2.2, Nkx6.1, Pax4, and Pax6 by Aire Ϫ/Ϫ MTEC was reduced to ϳ5% of WT levels. It is noteworthy that severe reductions in Pdx1 expression by the Aire-deficient MTEC population was mirrored by severe reductions in the expression of three endocrine structural genes, Ins, Sst, and Gip, that are directly regulated by Pdx1 and whose promoters are binding targets for Pdx1 (32)(33)(34). These results demonstrate that the genes affected by Aire deficiency in MTEC extend beyond structural products of peripheral lineages to include the regulatory elements that control expression of these genes in peripheral tissues.…”
Section: Aire Deficiency Leads To Severe Reductions In the Pancreaticmentioning
confidence: 77%
“…2C), where expression of Pdx1, Nkx2.2, Nkx6.1, Pax4, and Pax6 by Aire Ϫ/Ϫ MTEC was reduced to ϳ5% of WT levels. It is noteworthy that severe reductions in Pdx1 expression by the Aire-deficient MTEC population was mirrored by severe reductions in the expression of three endocrine structural genes, Ins, Sst, and Gip, that are directly regulated by Pdx1 and whose promoters are binding targets for Pdx1 (32)(33)(34). These results demonstrate that the genes affected by Aire deficiency in MTEC extend beyond structural products of peripheral lineages to include the regulatory elements that control expression of these genes in peripheral tissues.…”
Section: Aire Deficiency Leads To Severe Reductions In the Pancreaticmentioning
confidence: 77%
“…Three transcriptional factors, CREB, pancreatic and duodenal homeobox 1 (PDX1) and PAX6, have been identified as binding to the somatostatin promoter region between −109 and 100 [20][21][22] (Fig. 4c).…”
Section: /β2armentioning
confidence: 99%
“…A point mutation in the A-element that abolishes both PDX-1 and PBX binding has been shown to be unable to reduce the promoter activity (57). In contrast, a point mutation that selectively eliminates PDX-1 binding to a proximal B-element reduces the promoter activity.…”
Section: Somatostatinmentioning
confidence: 99%
“…Pax6 binding is essential for the promoter activity and a stop codon mutation in the A-element has been shown to reduce both Pax6 binding and somatostatin gene transcription. Andersen et al (57) proposed that the b/d-cellspecific activity of the SMS-UE is achieved through simultaneous binding of PDX-1 and Pax6 to the Band C-elements respectively. It has been demonstrated that PDX-1 forms a heterodimeric complex with PBX, the mammalian homologue of the Drosophila extradenticle.…”
Section: Somatostatinmentioning
confidence: 99%
See 1 more Smart Citation